L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Shikonin alleviates high-fat diet-induced vascular aging and dysfunction by inhibiting oxidative stress and mitochondrial damage - Guang-qiu Ren; Hui-jun Liu; Ya-qi Guo; Mei-ling He; Jiao Li; Zhan-xia Li; Chen-hui Jia; Tong Liu; Jing Yang (Molecular Biology Reports, 2026)

Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Hierarchical tubular carbon with differentiated Co/N/P functional units for selective silver recovery via capacitive electrosorption-reduction coupling - Linyi Ren; Yongping He; Fen Li; Lei Zhang; Ao Qiu; Xiayu Li; Xinhua Huang (Desalination, 2026)

Obliquity modulation pacing of mid–high-latitude lacustrine systems during the Late Paleozoic Ice Age - Renda Huang; Zhijun Jin; Ruoyuan Qiu; Xueyu Yao; Yinan Feng; Ren Wei; Mingsong Li; Youwei Wang (Global and Planetary Change, 2026)

A Novel ARTP-derived Bacillus megaterium Mutant with Enhanced Salt Tolerance and Plant Growth Promotion in Saline–alkali Soil - Min Sun; PengFei Qiu; XinJie Yuan; QiLi Zhu; ZhenXing Peng; JiMin Lv; HongShun Li; JunPing Bao; YanQing Wei; ShuDong Qu; XianShun Ren; ZiHao Wang; et al. (Current Microbiology, 2026)
Soil salinization seriously threatens global food security with continuously expanding affected areas. Bacillus megaterium -based bioinoculant serves as an eco-friendly strategy for saline–alkali land remediation, whereas wild-type (WT) strains generally exhibit poor salt–alkali tolerance. To address this limitation, atmospheric and room temperature plasma (ARTP) mutagenesis combined with a microbial microdroplet culture (MMC) high-throughput screening system was adopted to screen high salt-tolerant B. megaterium mutant followed by multi-omics characterization. Using WT B. megaterium LD (CGMCC No.21828) as the original strain, a mutant library was constructed via optimized ARTP treatment, and the elite mutant SLD48 was isolated under dynamically increasing salt gradients. Compared with the wild type, SLD48 possesses a larger genome of 6,252,538 bp and acquires 28 extra functional genes including spoIVCA and pJ_gene0003 . Intracellular osmoprotectants (proline, glycine betaine) and antioxidant α-tocopherol were markedly accumulated in SLD48. moreover, exogenous supplementation of these substances in the culture medium can effectively alleviate the damage caused by salt stress to the cells. In pot trials with saline–alkali soil, the rhizosphere colonization of SLD48 reached 3.52 × 10⁵ CFU/g (2.46-fold of LD), and maize shoot fresh weight increased by 40.5% after inoculation. Collectively, this work confirms that mutant SLD48 is a promising microbial resource for saline–alkali soil improvement and crop yield promotion.

Two-step pyrolysis enabled by bentonite catalysis for the co-production of bioactive humic acid and functional carbon-clay composites - Huanhuan Li; Jiarun Duan; Lijuan Zhang; Yong Wen; Yun Xiang; Chen Qiu; Junmei An; Zhiguo Guo; Yidong Cai; Changchun Ge; Xiaona Ren; Xinjiang Zhou; et al. (Environmental Research, 2026)

Linking the dietary inflammation index to sarcopenia in diabetes: mediation by body roundness index and evidence from complementary analyses - Yang Yang; Ren-hua Lv; Peng-min Liu; Yan-qiu Sun; Lu-ping Wang; Yu Yu; Li-mei Zhang; Xin-yang Zhang (European Journal of Applied Physiology, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Vapor-assisted dip-coating of wide-bandgap perovskites: Suppressing Back-diffusion of solute via optimized withdrawal speed - Shifu Zhang; Zexian Dong; Yicheng Qian; Dongrui Jiang; Jinzhao Li; Zhixin Ren; Sheng He; Haixiao Zhu; Yuan Qiu; Qian Zhao; Shougen Yin; Huanqi Cao (Chemical Engineering Journal, 2026)

Wide bandgap in window layers for efficient perovskite solar cells - Haixiao Zhu; Zhixin Ren; Tingting Huang; Yujie Wang; Jinzhao Li; Sheng He; Ke Liu; Yuan Qiu; Qian Zhao; Shougen Yin; Huanqi Cao (Chemical Engineering Journal, 2026)

ZIP14-VDAC2 mediates the transport of extracellular iron into mitochondria in hepatocytes under PFOS exposure - Yu Li; Min Yu; Junping Ren; Tianming Qiu; Jingyuan Zhang; Chenbing Wu; Jie Bai; Xiance Sun; Xiaofeng Yao (Chemico-Biological Interactions, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Alternative stable states in coral communities along a latitudinal gradient simplify sediment bacterial assemblages but stabilize biogeochemical functions - Wentao Zhu; Zihan Qiu; Pei Yang; Jingzhao Ke; Xiangbo Liu; He Zhao; Jiquan Lin; Yuxiao Ren; Duanjie Huang; Xiubao Li (Ocean & Coastal Management, 2026)

Sustainable catalyst design: Magnesia slag-doped MS-LDHs fabricated via pulsed laser trapping for efficient and green Cr(VI) adsorption - Ren-yun Zhang; Yan Liu; Zhi-yu Fan; Hong-xuan Xing; Ji-dong Li; Qiu-yu Huang; Zhe Jin; Ting-an Zhang (Journal of Cleaner Production, 2026)

Antifungal activity and action mechanism of thymol, a mycotoxin inhibitor, against Fusarium asiaticum - Jie Zhang; Fuhao Ren; Han Gao; Yige Li; Xiaoru Yin; Zehua Zhou; Ziyang Zhang; Hui Qiu; Yiqiang Cai; Larisa Shcherbakova; Vitaly Dzhavakhiya; Yabing Duan (Food Chemistry, 2026)

Potential mechanisms of taste changes in surimi gels with typical cross-linking degrees during frozen storage: Based on ice crystals, water migration, and intermolecular interactions - Xiaoying Luo; Yuelei Lei; Xiaodong Li; Guoyan Ren; Bin Zhang; Zhijun Qiu; Wenchao Liu; Shanbai Xiong; Yang Hu (Food Chemistry, 2026)

An AcMYB10-AcF3GT1/GST1 module restricts anthocyanin synthesis in the fruit flesh of kiwifruit - Xiao-tian Li; Zhi-xia Huang; Yu-xiao Zhai; Ya-ting Guo; Yi-tong Liu; Yan Zhang; Zhu Xie; Andrew C. Allan; Xue-ren Yin; Wen-qiu Wang (Plant Cell Reports, 2026)

Improved lightweight convolutional neural network models for the detection and evaluation of Fusarium head blight in wheat - Wang Zhang; Yi Ren; Zidi Guo; Han Li; Man Zhang; Jie Liu; Ruicheng Qiu (Journal of Zhejiang University-SCIENCE B, 2026)

Strongly spatial-confined self-assembled monolayers for high-performance perovskite photovoltaics - Dongyang Li; Qiming Yin; Zhiwei Ren; Guihua Zhang; Jie Li; Qianyi Li; Yu Han; Sibo Li; Lihan Pang; Hao Xia; Guang Yang; Longbin Qiu; et al. (Science Bulletin, 2026)

Modified Fly Ash Regulates Enzyme Stoichiometry and Alleviates Microbial carbon-phosphorus Limitation in saline-alkali Soils - Enliang Ren; Ruxin Zhang; Yanhong Wang; Li Wang; Xuanhao Qiu; Zhongyi Qu (Journal of Soil Science and Plant Nutrition, 2026)

Dietary silymarin improves gut–liver health by enhancing intestinal barrier integrity and modulating TLR4/NF-κB and NLRP3-mediated inflammatory responses in Aeromonas hydrophila–infected grass carp - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Yun Zhang; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Host-associated volatile cues drive foraging behavior of Trichopria drosophilae toward Drosophila suzukii-infested fruits - Hai-Kuan Sun; Fan Yang; Ze-Hua Wang; Ren Li; Guang-Hang Qiao; Qiu-Fei Li; Yu-Yu Wang; Shan-Ning Wang (Journal of Pest Science, 2026)

PK/PD study of ceftazidime/avibactam in patients with severe intra-abdominal infections treated by continuous veno–venous hemofiltration - Sai Tian; Yong Chen; Mingjie Qiu; Wenqi Wu; Liuqing Dou; Jiajie Wang; Li Xu; Zhitao Zhou; Meilin Wu; Jiayang Li; Xiuwen Wu; Jianan Ren (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The histone demethylase KDM4A promotes esophageal cancer progression by epigenetically activating LRG1-mediated TGF-β signaling - Yueting Han; Huiya Wang; Yaoyang Guo; Hongdian Zhang; Xinyi Wen; Miao Zhang; Zhanhua Gao; Jie Hao; Minghan Qiu; Li Ren; Dongzhi Hu; Yi Ba; et al. (Apoptosis, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

The Hippo pathway in cardiac fibrosis: mechanisms and therapeutic prospects - Yuting Qiu; Shanshan Hu; Hui Li; Jiatong Ren; Meixi Liao; Jie Huo; Zenan Luo; Lili Lu (Human Cell, 2026)

Cauliflower mushroom ( Sparassis ): a promising functional food with nutritional and medicinal properties - Zhiheng Qiu; Xiaoyan Zhang; Shuhua Ren; Bei Jiang; Jiazhi Zhao; Meijuan Zhu; Di Zhou; Qian Li; Miao Zhang; Tianlai Li; Lili Shu (Critical Reviews in Food Science and Nutrition, 2026)

SETD2 inhibited T-cell acute lymphocytic leukemia invasion and infiltration by inhibiting the JAK/STAT pathway - Ling Qiu; Shihui Ren; Mengjiao Li; Baitao Dou; Dan Chen; Nan Zhang; Jiao Cai; Hao Yao; Fangyi Fan (Molecular and Cellular Biochemistry, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

Dielectric breakdown strength and energy storage improvement of polyimide through environmentally benign reactive ion etching plasma surface modification - Sen Ren; Yaogong Wang; Yan Qiu; Boya Zhang; Yixuan Li; Chenxi Liu; Lixia Pang; Di Zhou; Yongdong Li (Chemical Engineering Journal, 2026)

Gcm1 Orchestrates Lef1 Expression in Folate Deficiency-Induced Neural Tube Defects - Zhihua Cao; Lu Li; Xiaolong Gu; Baolian Li; Qi Xie; Xuefen Wu; Xinhuan Zhang; Guohua Zhang; Ke Wu; Wenbing Ren; Zhizhen Liu; Aili Fang; et al. (Molecular Neurobiology, 2026)

Migration and transformation of heavy metals and metalloids in soil and alfalfa (Medicago sativa L.)—mediated by citric acid–lanthanum–modified fly ash—and assessment of ecological safety thresholds - Enliang Ren; Ruxin Zhang; Xuanhao Qiu; Li Wang; Junjie Li; Yibo Zhao; Liping Wang; Zhongyi Qu (Journal of Environmental Chemical Engineering, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

BS-D275: A novel locus on the chromosome arm 2DS governing branched spike development in wheat - Yunfeng Qu; Yongkang Ren; Jinghuang Hu; Yi Liu; Dan Qiu; Yahui Li; Qiuhong Wu; Miao He; Qing Guo; Yu Sun; Wenze Yan; Zhaohui Tang; et al. (Theoretical and Applied Genetics, 2025)

Genomic Insights into Azole Resistance Mechanisms in Candida tropicalis Among Hematological Malignancy Patients with Candidemia - Yalu Ren; Qiongfang Zhu; Yining Wu; Li Ju; Jia Liu; Meili Shen; Weiwei Wu; Jun Qiu; Jie Xu (Current Microbiology, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

High-content coal gasification slag-based cemented paste backfill synthesized with calcium carbide residue and glauber’s salt - Qingbo Liu; Junchen Xiang; Wenrun Li; Biqi Ren; Zhengyu Ma; Jingping Qiu (Process Safety and Environmental Protection, 2025)

Temporal dynamics of gonadal development and reproduction of wild Manila clam (Ruditapes philippinarum) in the Xiaoqing River estuary, Laizhou Bay - Lulei Liu; Suyan Xue; Ang Li; Yushui Ren; Ling Zhu; Jiaqi Li; Longzhen Liu; Yuze Tang; Yanguo Qiu; Yuze Mao (Estuarine, Coastal and Shelf Science, 2025)

Effects of Exogenous Azelaic Acid (AzA) Application on 2-Acetyl-1-Pyrroline (2AP) Content, the Antioxidant Defense System, and Yield in Fragrant Rice - Qingqing Li; Hui Hu; Xuexue Wang; Fanglin Liu; Mingruo Sun; Yong Ren; Xianjin Qiu (Journal of Plant Growth Regulation, 2025)

Reducing arsenic mobilization in sediments: A synergistic effect of oxidation and adsorption with zirconium-manganese binary metal oxides - Xue Jiang; Youzi Gong; Jiaxing Xiong; Boxian Ren; Yewei Qiu; Zhiguo Lin; Ying Tang; Shixiong Wang; Xiaolong Wang; Cai Li; Xiangjun Yang; Shiming Ding (Water Research, 2025)

Transcriptional factors AcNAC1/2 synergistically orchestrate kiwifruit chlorophyll degradation - Ying-ying Wu; Shi Wu; Xin-yi Li; Jia-hui Deng; Pu Liu; Wen-qiu Wang; Xue-ren Yin; Xiao-fen Liu (Postharvest Biology and Technology, 2025)

Urinary monohydroxylated polycyclic aromatic hydrocarbons among healthy elderly in the China BAPE study: Exposure characteristics, influencing factors, and health risks - Jiankun Qian; Xiaojie Guo; Chenglei Qi; Peijie Sun; Chenfeng Li; Chenlong Li; Kangning Cao; Yibo Xu; Huimin Ren; Jiran Zhang; Yu Wang; Shan Bao; et al. (Journal of Hazardous Materials, 2025)

“Framework Channel catalysis”: A multiphase synergistic Zn-based coating strategy for high-performance zinc-ion batteries - Yue Shi; Le Li; Chao Tan; Conghui Wang; Yuanyuan Yang; Haoyuan Du; Mengyao Guo; Xiaohu Yu; Zhigui Ren; Yongqiang Ji; Guotai Sun; Hengwei Qiu; et al. (Chemical Engineering Journal, 2025)

The ultrastructure of the Cretaceous feathers highlights the evolution of the feather - Jiajia Wang; Rui Qiu; Qian Chen; Di Liu; Tongbo Zhang; Ying Li; Xinjun Zhang; Baopeng Wang; Dongyu Hu; Dong Ren; Xiaolin Wang; Xiaofei Xia; et al. (Science Bulletin, 2025)

Ultrathin and oxygen vacancies rich layer of p-n heterojunction boosts urea-powered green hydrogen production - Lang Gan; Chenmeng Jiang; Jincheng Liu; Wei Chen; Yanjie Ren; Jiawang Li; Jiafeng Tian; Wei Chen; Jincheng Huang; Jing Zhao; Kang Chen; Wei Qiu; et al. (Chemical Engineering Journal, 2025)

Unraveling individual and combined toxicity of microplastics and tetracycline at environment-related concentrations to coral holobionts - Shiqi Jiang; Lei He; Linglong Cao; Ruikun Sun; Zhenqing Dai; Yan-Qiu Liang; Lei Ren; Shengli Sun; Chengyong Li (Journal of Hazardous Materials, 2025)

New perspectives on the immune regulatory role of dietary silymarin in the intestines of juvenile grass carp (Ctenopharyngodon idella) - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Exposure profiles, determinants, and health risks of chemicals in personal care products among healthy older adults from the China BAPE study - Xiaojie Guo; Jiankun Qian; Huimin Ren; Enmin Ding; Xiao Ma; Jiran Zhang; Tian Qiu; Yifu Lu; Peijie Sun; Chenfeng Li; Chenlong Li; Yibo Xu; et al. (Journal of Hazardous Materials, 2025)

New insight of surface water disinfection by Fe2+-SPC: Important role of carbonate radical and the influence of carbonate/bicarbonate ions on free radicals balance - Zixiao Ren; An Ding; Xu He; Piotr Oleskowicz-Popiel; Guibai Li; Heng Liang; Huu Hao Ngo; Wei Qiu (Journal of Environmental Management, 2025)

Report of two coinfections of human adenovirus and sapovirus in patients with acute gastroenteritis from China - Xin Wang; Yaqing He; Mingda Hu; Wanqiu Liu; Kexin Li; Qiao Li; Shaofu Qiu; Lianqun Jin; Hailong Zhang; Boqian Wang; Chuanfu Zhang; Zhixi Peng; et al. (Genes & Genomics, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Conventional and genetic association between migraine and stroke with druggable genome-wide Mendelian randomization - Xiaoyu Wang; Wendu Pang; Xin Hu; Tao Shu; Yaxin Luo; Junhong Li; Lan Feng; Ke Qiu; Yufang Rao; Yao Song; Minzi Mao; Yuyang Zhang; et al. (Human Genetics, 2025)

Holocene variability in sea-ice cover and Pacific water inflow and their impacts on productivity in the Chukchi Sea - Dongling Li; Yuanhui Huang; Jian Ren; Yanguang Liu; Yue Qiu; Weiguo Wang; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Charge signals characterizing the influence of bedding angles on shale damage under cyclic loading and unloading - Long Ren; Baolong Zhu; Jing Li; Liming Qiu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Dual-ion permeation Janus membrane-assisted element reconstitution system enables fluorosilicate-oriented recovery from fluoride-rich and silica-rich wastewaters - Yangbo Qiu; Chao Wang; Ran Li; Lidong Feng; Shuaijun Yu; Jiangnan Shen; Long-Fei Ren; Jiahui Shao (Water Research, 2025)

Intra- and inter-annual spatiotemporal variations and climatic driving factors of surface water area in the Irtysh River Basin during 1985–2022 - Enzhao Zhu; Alim Samat; Wenbo Li; Ren Xu; Junshi Xia; Yinguo Qiu; Jilili Abuduwaili (Remote Sensing Applications: Society and Environment, 2025)

Analysis of the softening-melting mechanism of cold-bonded briquette from return sinter fines - Ying Li; Dejin Qiu; Manqing Li; Yuandong Xiong; Timo Fabritius; Su Cao; Ang Li; Abdallah Ahmed Elsherbiny; Jie Ren; Han Wei; Yaowei Yu (Journal of Cleaner Production, 2025)

Synergy between single atom and nanoclusters promotes power and CO tolerant performance in PEMFCs - Jiwen Lin; Zhongyao Zhang; Jiaye Qiu; Yujie Wu; Jun Yu; Yongliang Li; Xiangzhong Ren; Lei Zhang; Zhongxin Song (Chemical Engineering Journal, 2025)

Effect of combined treatments of hydrolysis and succinylation on the solubility and emulsion stability of rennet casein and micellar casein - Hongjuan Li; Chuan Ren; Dongyu Hou; Xiaobao Qiu; Juan Zhang; Xiaohong Chen; Yang Zou; Guilian Sun; Kewen Li; Hongbo Li; Jinghua Yu (Food and Bioproducts Processing, 2024)

Developing high-flux dense Janus membrane with robust wetting and scaling resistance: A systematic comparison with Omniphobic membranes - Chao Wang; Yangbo Qiu; Chenglin Zhang; Feng Li; Long-Fei Ren; Jiahui Shao (Desalination, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

A transdermal fullerenol emulsion-mediated angiogenesis mitigates radiation-induced skin injury - Haijun Peng; Haiyang Jiang; Ying Li; Xiaobo Wang; Die Ma; Junsong Guo; Biao Li; Hao Wang; You Liao; Chenglu Gu; Dongmei Wang; Hui Xu; et al. (Chemical Engineering Journal, 2024)

Bioinformatics Approach to Identify the Pathogenetic Link of Gut Microbiota-Derived Short-Chain Fatty Acids and Ischemic Stroke - Liang Ding; Jianing Wang; Sha Qiu; Zhizhen Ren; Yuantao Li; Pengpeng An (Molecular Neurobiology, 2024)
Stroke is a life-threatening condition that impairs the arteries and causes neurological impairment. The incidence of stroke is increasing year by year with the arrival of the aging population. Thus, there is an urgent need for early stroke diagnosis. Short-chain fatty acids (SCFAs) can modulate the central nervous system and directly and indirectly impact behavioral and cognitive functions. This study aimed to investigate the connection between SCFA metabolism and stroke development via bioinformatic analysis. Initially, the Gene Set Enrichment Analysis (GSEA) and immune cell infiltration analysis were performed based on RNA data from stroke patients to comprehend the mechanisms governing stroke pathogenesis. The functional analysis, including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Protein-Protein Interaction (PPI), was performed based on the Differentially Expressed Gene (DEG) selected by the limma package. 1220 SCFA metabolism-related genes screened from Genecards databases were intersected with 242 genes in main modules determined by Weighted Gene Co-Expression Network Analysis (WGCNA), and the final 10 SCFA key genes were obtained. GO analysis revealed that these genes were involved in immune response processes. Through lasso regression analyses, we established a stroke early diagnosis model and selected 6 genes with diagnostic value. The genes were validated by the area under curve (AUC) values and had a relatively good diagnostic performance. Finally, 4 potential therapeutic drugs targeting these genes were predicted using the Drug Signatures Database (DSigDB) via Enrichr. In conclusion, this paper analyzes the involvement of SCFAs in the complex gut-brain axis mechanism, which contributes to developing new targets for treating central nervous system diseases and provides new ideas for early ischemic stroke diagnosis.

Two ethylene-responsive transcription factors, AdVAL2 and AdKAN2, regulate early steps in kiwifruit starch degradation - Yang Tong; Wen-yue Su; Yu-tong Chen; Xiao-fen Liu; Qiu-yun Zhang; Tong-hui Qi; Andrew C. Allan; Xiang Li; Xue-ren Yin (Postharvest Biology and Technology, 2024)

Novel visible-light activated photocatalytic ultrafiltration membrane for simultaneous separation and degradation of emerging contaminants - Ran Li; Zhidong Wei; Peng Li; Yangbo Qiu; Chengyi Wang; Chao Wang; Long-Fei Ren; Jiahui Shao; Yiliang He (Journal of Hazardous Materials, 2024)

Enhancing biodegradation efficiency of PLA/PBAT-ST20 bioplastic using thermophilic bacteria co-culture system: New insight from structural characterization, enzyme activity, and metabolic pathways - Yizhan Qiu; Pan Wang; Luxi Zhang; Chunmei Li; Jiaxin Lu; Lianhai Ren (Journal of Hazardous Materials, 2024)

Effect of ethanol addition on the physicochemical, structural and in vitro digestive properties of Tartary buckwheat starch-quercetin/rutin complexes - Libo Wang; Yilin Huang; Yanjuan Ren; Haoran Wang; Yue Ding; Guangyue Ren; Tongtong Wang; Zaigui Li; Ju Qiu (Food Chemistry, 2024)

Design of multifunctional theranostic nanoplatforms with glutathione-triggered H2S generation and H2S-activitated multi-modal therapy - Cheng Tao; Qian Ren; Nuo Yu; Mei Wen; Pu Qiu; Shining Niu; Zhigang Chen; Kun Li; Dong Xie (Chemical Engineering Journal, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

New perspectives on the role of vitamin D in the mucosal barrier system of fish gills infected with Flavobacterium columnare - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Novel electrocatalytic capacitive deionization with catalytic electrodes for selective phosphonate degradation: Performance and mechanism - Chengyi Wang; Siyue Xue; Yubo Xu; Ran Li; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Water Research, 2024)

Preparation and characterization of whey protein isolate-dextran-proanthocyanidins ternary complexes: Formation mechanism, physicochemical stability - Hongjuan Li; Juan Zhang; Yifei Wu; Chuan Ren; Xiaobao Qiu; Hongbo Li; Guilian Sun; Kewen Li; Jinghua Yu (Food Hydrocolloids, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Effects of 90 dB pure tone exposure on auditory and cardio-cerebral system functions in macaque monkeys - Weijia Zhi; Ying Li; Yuchen Wang; Yong Zou; Haoyu Wang; Xinping Xu; Lizhen Ma; Yanling Ren; Yefeng Qiu; Xiangjun Hu; Lifeng Wang (Environmental Research, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Electronic structure regulation of Fe single atom coordinated nitrogen doping MoS2 catalyst enhances the Fenton-like reaction efficient for organic pollutant control - Shunlin Li; Hui Wang; Congcong Qiu; Jianan Ren; Yiyin Peng; Yang Liu; Fangyuan Dong; Zhaoyong Bian (Journal of Hazardous Materials, 2024)

Effects of Fe3O4 NMs based Fenton-like reactions on biodegradable plastic bags in compost: New insight into plastisphere community succession, co-composting efficiency and free radical in situ aging theory - Jiaxin Lu; Yizhan Qiu; Luxi Zhang; Jiancheng Wang; Chunmei Li; Pan Wang; Lianhai Ren (Journal of Hazardous Materials, 2024)

Facile preparation of AlCo-LDH/sepiolite composites as peroxymonosulfate catalysts for efficient degradation of norfloxacin: Performance, reaction mechanism and degradation pathway - Yubo Wang; Long Zhang; Zijuan Qiu; Xiaofei Ren; Junying Song; Dengzheng Gao; Qingbin Guo; Li Wang; Xiaolong Hu (Journal of Environmental Chemical Engineering, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Accelerating the generation of NiOOH by in-situ surface phosphating nickel sulfide for promoting the proton-coupled electron transfer kinetics of urea electrolysis - Xin Guo; Longyu Qiu; Menggang Li; Fenyang Tian; Xue Ren; Sheng Jie; Shuo Geng; Guanghui Han; Yarong Huang; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2024)

Revealing the role of crystal chemistry in REE fractionation in skarn garnets: insights from lattice-strain theory - Guang Wen; Jun Qiu; Albert H. Hofstra; Daniel E. Harlov; Zhe Ren; Jian-Wei Li (Contributions to Mineralogy and Petrology, 2024)

Meroterpenoids with divers' rings systems from Phyllosticta capitalensis and their anti-inflammatory activity - Xiao-xia Zhu; Wan-qiu Liu; Zhao-xia Shi; Huang-yao Zhu; Si-qi Fan; Jie Zhang; Wen-yuan Liu; Li-Jun Xu; Qing-Jia Ren; Feng Feng; Jian Xu (Phytochemistry, 2024)

Effective electrosorption and recovery of phosphorus by capacitive deionization with a covalent organic framework-membrane coating electrode - Chengyi Wang; Ran Li; Yubo Xu; Zhongbao Ma; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Desalination, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Organic anion transporting polypeptide 3a1 is a novel influx pump for Perfluorooctane sulfonate in Sertoli cells and contributes to its reproductive toxicity - Ting Li; Lianlian Jiang; Shaokai Zheng; Chong Qiu; Nannan Zhao; Xiaojun Lin; Hang Ren; Jiyan Huang; Hongxia Wang; Lianglin Qiu (Chemosphere, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Monocarboxylate transporter blockage-enabled lactate redistribution reshapes immunosuppressive tumor microenvironment and enhances chemodynamic immunotherapy - Jingxue Wang; Weixi Jiang; Mingxiao Fang; Chier Du; Xun Guo; Xiaoling Qiu; Xiaoting Wang; Yuanli Luo; Peng Tu; Chen Cheng; Pan Li; Haitao Ran; et al. (Chemical Engineering Journal, 2023)

Unravelling chilling-stress resistance mechanisms in endangered Mangrove plant Lumnitzera littorea (Jack) Voigt - Xinhui Xia; Lulu Hao; Yifei Sun; Yiqing Lv; Yihong Wang; Haiyu Wu; Zongjin Jiang; Xinru Li; Yuhan Yan; Xiaojian Chen; Binghou Li; Hao Li; et al. (Marine Environmental Research, 2023)

Resveratrol-loaded nanoplatform RSV@DTPF promote alveolar bone regeneration in OVX rat through remodeling bone-immune microenvironment - Haoran Peng; Xinyi Qiu; Mingyue Cheng; Yue Zhao; Lutong Song; Bijun Zhu; Yuyang Li; Chao Liu; Shuangshuang Ren; Leiying Miao (Chemical Engineering Journal, 2023)

Laser boosting the influx of calcium ions to enhance gasdermin e-dependent pyroptosis driven by a dual-layer polydopamine nanoagonist - Xiaoling Qiu; Weixi Jiang; Xun Guo; Chier Du; Xiaoting Wang; Yu Tian; Hongjin An; Jingxue Wang; Yuanli Luo; Yuan Guo; Peng Luo; Hua Teng; et al. (Chemical Engineering Journal, 2023)

Hyperspectral images classification of small sample based on the strategy of sample enlargement by superpixel pair method - Xueying Li; Pingping Fan; Zongmin Li; Huimin Qiu; Guangli Hou; Guangyuan Chen; Guoxing Ren (International Journal of Remote Sensing, 2023)

Reduced bacterial resistance antibiotics with improved microbiota tolerance in human intestinal: Molecular design and mechanism analysis - Meijin Du; Zhixing Ren; Qing Li; Qikun Pu; Xinao Li; Youli Qiu; Yu Li (Journal of Hazardous Materials, 2023)

Freeze-thaw cycle effects on granite and the formation mechanism of long-runout landslides: insights from the Luanshibao case study in the Tibetan Plateau, China - Changbao Guo; Yongshuang Zhang; Yanan Zhang; Zhongkang Wu; Xiang Li; Ruian Wu; Yiqiu Yan; Zhendong Qiu; Sanshao Ren; Wenbo Zhao (Bulletin of Engineering Geology and the Environment, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Performance of RC beam-column assemblies during and after elevated temperature to resist progressive collapse - Liu Jin; Dong-Qiu Lan; Ren-Bo Zhang; Jian Li; Kai Qian (Engineering Structures, 2023)

Oocyte Arrested at Metaphase II Stage were Derived from Human Pluripotent Stem Cells in vitro - Xiaoli Yu; Ning Wang; Xiang Wang; Hehe Ren; Yanping Zhang; Yingxin Zhang; Yikai Qiu; Hongyan Wang; Guoping Wang; Xiuying Pei; Ping Chen; Yahui Ren; et al. (Stem Cell Reviews and Reports, 2023)
Initiation of meiosis is the most difficult aspect of inducing competent oocytes differentiation from human stem cells in vitro . Human induced pluripotent stem cells (hiPSCs) and embryonic stem cells (hESCs) were cultured with follicle fluid, cytokines and small molecule to induced oocyte-like cells (OLCs) formation through a three-step induction procedure. Expression of surface markers and differentiation potential of germ cells were analyzed in vitro by flow cytometry, gene expression, immunocytochemistry, western blotting and RNA Sequencing. To induce the differentiation of hiPSCs into OLCs, cells were firstly cultured with a primordial germ cell medium for 10 days. The cells exhibited similar morphological features to primordial germ cells (PGCs), high expressing of germ cell markers and primordial follicle development associated genes. The induced PGCs were then cultured with the primordial follicle-like cell medium for 5 days to form the induced follicle-like structures (iFLs), which retained both primordial oocytes-like cells and granulosa-like cells. In the third step, the detached iFLs were harvested and transferred to the OLC-medium for additional 10 days. The cultured cells developed cumulus-oocyte-complexes (COCs) structures and OLCs with different sizes (50–150 μm diameter) and a zona pellucida. The in vitro matured OLCs had polar bodies and were arrested at metaphase II (MII) stage. Some OLCs were self-activated and spontaneously developed into multiple-cell structures similar to preimplantation embryos, indicating that OLCs were parthenogenetically activated though in vitro fertilization potential of OLCs are yet to be proved. in vitro maturation of OLCs derived from hiPSCs provides a new means to study human germ cell formation and oogenesis. Graphical Abstract

15,16-dihydrotanshinone I in Danshen ethanol extract aggravated cholestasis by inhibiting Cyp3a11 mediated bile acids hydroxylation - Yue Li; Qian Wang; Jingyi Jin; Bo Tan; Jie Ren; Guochao Song; Bin Zou; Fengyi Weng; Dongming Yan; Furong Qiu (Toxicology Letters, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Magnesium Hydroxide Slurry Coagulation-Adsorption Performance for Reactive Orange Removal Assisted with PAM - Xiaoli Deng; Jianhai Zhao; Xiuming Qiu; Yingying Duan; Xiaoyu Ren; Wenpu Li; Rong Mu; Hongying Yuan (Water, Air, & Soil Pollution, 2023)

Performance and mechanism of sacrificed iron anode coupled with constructed wetlands (E-Fe) for simultaneous nitrogen and phosphorus removal - Ming Zhou; Jiashun Cao; Yuanyuan Qiu; Yanhong Lu; Jinyan Guo; Chao Li; Yantang Wang; Liangshan Hao; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Bibliometric overview of research progress, challenges, and prospects of rural domestic sewage: Treatment techniques, resource recovery, and ecological risk - Le Zhong; Jie Ding; Tong Wu; Yi-lin Zhao; Ji Wei Pang; Ji-Ping Jiang; Jun-Qiu Jiang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Water Process Engineering, 2023)

Performance and mechanisms of biochar-assisted vermicomposting in accelerating di-(2-ethylhexyl) phthalate biodegradation in farmland soil - Zhen Zhen; Shuwen Luo; Yijie Chen; Gaoyang Li; Huijun Li; Ting Wei; Fengcheng Huang; Lei Ren; Yan-Qiu Liang; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2023)

Black soldier fly larvae replace traditional iced trash fish diet to enhance the delicious flavor of Chinese mitten crab (Eriocheir sinensis) - Jian-Feng Qiu; Cheng Luo; Li-Hua Ren; Wei Li; Tai-Ming Dai; Guang Wang; Xiao-Ning Sun; Kou-Chang Chong Moua; Yang-Hu Sima; Shi-Qing Xu (Frontiers in Marine Science, 2023)
Chinese mitten crabs ( Eriocheir sinensis ) are traditionally fed iced trash fish, but the industry is facing problems such as low breeding safety. Black soldier fly ( Hermetia illucens ) is an alternative protein source in animal diets, including diets for aquatic animals, due to its high nutritional value. However, studies on the effects of black soldier fly on the flavor characteristics of aquatic animals are still limited. In the present study, we investigated the effects of the complete replacement of iced trash fish with black soldier fly larvae during the fattening period of Chinese mitten crab on the flavor molecule contents and evaluation indices. The levels of free amino acids and nucleotides were determined in three edible parts (muscle, hepatopancreas, and gonads) of crab. Taste activity value analysis showed that glutamic acid, glycine, alanine, and arginine were the main amino acids contributing to the umami taste and sweetness, while histidine, lysine, valine, and methionine were the main amino acids contributing to the bitterness. Equivalent umami concentration (EUC) analysis showed that female gonads had the strongest umami taste, followed by the hepatopancreas and muscle. Sweetness value (SWT) analysis showed that the sweetness of muscle was the highest. Feeding black soldier fly larvae affected the flavor characteristics of crabs with tissue and sex differences. The EUC of the female gonads and SWT of the muscle were significantly increased. Meanwhile, the EUC of the hepatopancreas and SWT of the gonads were slightly decreased in male crabs. Our results indicate that the complete replacement of iced trash fish with black soldier fly larvae during the fattening period significantly enhances the flavor characteristics of crabs based on the contents of flavoring amino acids and nucleotides. It is important for sustainable aquaculture to replace animal protein with alternative protein sources such as black soldier fly larvae.

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Correction to: Soybean genetic resources contributing to sustainable protein production - Bingfu Guo; Liping Sun; Siqi Jiang; Honglei Ren; Rujian Sun; Zhongyan Wei; Huilong Hong; Xiaoyan Luan; Jun Wang; Xiaobo Wang; Donghe Xu; Wenbin Li; et al. (Theoretical and Applied Genetics, 2022)

Soybean genetic resources contributing to sustainable protein production - Bingfu Guo; Liping Sun; Siqi Jiang; Honglei Ren; Rujian Sun; Zhongyan Wei; Huilong Hong; Xiaoyan Luan; Jun Wang; Xiaobo Wang; Donghe Xu; Wenbin Li; et al. (Theoretical and Applied Genetics, 2022)
Key message Genetic resources contributes to the sustainable protein production in soybean. Abstract Soybean is an important crop for food, oil, and forage and is the main source of edible vegetable oil and vegetable protein. It plays an important role in maintaining balanced dietary nutrients for human health. The soybean protein content is a quantitative trait mainly controlled by gene additive effects and is usually negatively correlated with agronomic traits such as the oil content and yield. The selection of soybean varieties with high protein content and high yield to secure sustainable protein production is one of the difficulties in soybean breeding. The abundant genetic variation of soybean germplasm resources is the basis for overcoming the obstacles in breeding for soybean varieties with high yield and high protein content. Soybean has been cultivated for more than 5000 years and has spread from China to other parts of the world. The rich genetic resources play an important role in promoting the sustainable production of soybean protein worldwide. In this paper, the origin and spread of soybean and the current status of soybean production are reviewed; the genetic characteristics of soybean protein and the distribution of resources are expounded based on phenotypes; the discovery of soybean seed protein-related genes as well as transcriptomic, metabolomic, and proteomic studies in soybean are elaborated; the creation and utilization of high-protein germplasm resources are introduced; and the prospect of high-protein soybean breeding is described.

High-resolution numerical simulation of topographic influence on the heavy rainfall of Typhoon Rammasun - Xianling Jiang; Fumin Ren; Wenyu Qiu; Liguang Wu; Zhuguo Ma; Xun Li (Theoretical and Applied Climatology, 2022)

URANS Calculation of Ship Heave and Pitch Motions in Marine Simulator Based on Overset Mesh - Ziping Wang; Tingqiu Li; Junsheng Ren; Qiu Jin; Wenjun Zhou (Journal of Marine Science and Engineering, 2022)
So as to improve the reliability and accuracy of marine simulators, it is essential to predict ship heave and pitch motions in regular waves. The motions of two ships, the international standard model KVLCC2 and the first training ship, “Yukun”, of Dalian Maritime University, are simulated using a three-dimensional (3D) numerical wave tank based on the Unsteady Reynolds Averaged Navier–Stokes (URANS) equations. The free surface is captured by the volume of fluid (VOF) method, and an SST k-ω turbulence model is used to describe the turbulence flow. The numerical model is first validated for the standard KVLCC2 at three different speeds through a comparison with the published experimental data and the potential flow results. Then, numerical simulation is performed for the motion of the ship Yukun with different speeds under various sea conditions. The heave amplitude of the hull changes with the increase in the wavelength when the maximum value is reached. Upon comparing the RAOs of ship motions under different wave steepness conditions, it is apparent that the heave and pitch motions of ships nonlinearly decrease with an increase in wave steepness. The results were added to the database of the marine simulator to further improve the accuracy and realism of the simulator.

Spatiotemporal distribution of sea-island prehistoric dune sites, Holocene sea levels, and aeolian sand activities in Fujian Province, China - Jianhui Jin; Zhiyong Ling; Zhizhong Li; Xinxin Zuo; Xuechun Fan; Yunming Huang; Xiaoyang Wang; Changfu Wei; Yongqing Ren; Junjie Qiu (Journal of Geographical Sciences, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Simultaneous determination of praziquantel and its main metabolites in the tissues of black goats and their residue depletion - Tong-Yan Ding; Xiao-Gui Shu; Ren-Ping Xiong; Jing-Li Qiu; Lu Li; Li-Min He (Food Additives & Contaminants: Part A, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Expansion of bilin‐based red light sensors in the subaerial desert cyanobacterium Nostoc flagelliforme - Hai‐Feng Xu; Guo‐Zheng Dai; Yu‐Jie Wang; Chao Cheng; Jin‐Long Shang; Ren‐Han Li; Ke Liu; Deqiang Duanmu; Bao‐Sheng Qiu (Environmental Microbiology, 2022)
Summary Light is the crucial environmental signal for desiccation‐tolerant cyanobacteria to activate photosynthesis and prepare for desiccation at dawn. However, the photobiological characteristics of desert cyanobacteria adaptation to one of the harshest habitats on Earth remain unresolved. In this study, we surveyed the genome of a subaerial desert cyanobacterium Nostoc flagelliforme and identified two phytochromes and seven cyanobacteriochromes (CBCRs) with one or more bilin‐binding GAF (cGMP phosphodiesterase/adenylyl cyclase/FhlA) domains. Biochemical and spectroscopic analyses of 69 purified GAF‐containing proteins from recombinant phycocyanobilin (PCB), biliverdin or phycoerythrobilin‐producing Escherichia coli indicated that nine of these proteins bind chromophores. Further investigation revealed that 11 GAFs form covalent adducts responsive to near‐UV and visible light: eight GAFs contained PCB chromophores, three GAFs contained biliverdin chromophores and one contained the PCB isomer, phycoviolobilin. Interestingly, COO91_03972 is the first‐ever reported GAF‐only CBCR capable of sensing five wavelengths of light. Bioinformatics and biochemical analyses revealed that residue P132 of COO91_03972 is essential for chromophore binding to dual‐cysteine CBCRs. Furthermore, the complement of N . flagelliforme CBCRs is enriched in red light sensors. We hypothesize that these sensors are critical for the acclimatization of N . flagelliforme to weak light environments at dawn.

Dynamic Neutrophil–Lymphocyte Ratios Predict Short-term Prognostic Outcome of Thrombolysis in Patients with Acute Ischemic Stroke - Yiyun Weng; Jingyu Hu; Junli Ren; Honghao Huang; Chenguang Yang; Jiamin Shen; Wenjing Pan; Fangyue Sun; Haojie Qiu; Yufan Gao; Shengqi Li; Xuerong Huang; et al. (Neurotoxicity Research, 2021)

Extensional tectonics and North China Craton destruction: Insights from the magnetic susceptibility anisotropy (AMS) of granite and metamorphic core complex - Wei Lin; Jipei Zeng; Lingtong Meng; Huabiao Qiu; Wei Wei; Zhiheng Ren; Yang Chu; Shuangjian Li; Chao Song; Qincheng Wang (Science China Earth Sciences, 2021)

Integrated transcriptome and miRNA sequencing approaches provide insights into salt tolerance in allotriploid Populus cathayana - Tong Qiu; Kang Du; Yanchun Jing; Qingqing Zeng; Zhao Liu; Yun Li; Yongyu Ren; Jun Yang; Xiangyang Kang (Planta, 2021)

Risk factors for sleep disorders in patients undergoing peritoneal dialysis - Gui-Ling Liu; Qiu-Nan Zhan; You-Lu Zhao; Zu-Ying Xiong; Jin-Lan Liao; Ye-Ping Ren; Qin Wang; Li-Ping Duan; Zhao-Xia Zheng; Li Hao; Jie Dong (Sleep and Biological Rhythms, 2021)
Sleep disorders in patients with end-stage renal disease are common but have rarely been reported in previous studies. Therefore, we examined the prevalence of sleep disorders and the risk factors for declining sleep quality in patients undergoing peritoneal dialysis (PD). A multicenter prospective cohort study was conducted at five PD centers across different provinces in China. A total of 449 patients who underwent PD between March to November 2013 were enrolled. Demographic data, laboratory indicators, presence of depression, and sleep assessment data were collected. Sleep questionnaires reflecting five categories of sleep disorders, namely, insomnia, restless legs syndrome, excessive daytime sleepiness, possible narcolepsy, and sleepwalking and nightmares, were administered at baseline and at 24 months postoperatively. Sleep disorders were diagnosed when a patient had at least one sleep problem. At baseline, 335 (74.6%) patients had at least one type of sleep disorder. Depression, diabetes mellitus (DM), and male were found to be associated with the presence of a sleep disorder. At follow-up, the prevalence of insomnia, restless legs syndrome, and excessive daytime sleepiness had significantly increased in 285 patients. Furthermore, cardiovascular disease (CVD) was found to be associated with the presence of sleep disorders in patients with one or more disorders at baseline, whereas a low serum albumin level was found to be associated with sleep disorders in patients without any sleep disorders at baseline. The prevalence of sleep disorders was relatively high among PD patients at baseline and increased afterthe2-year follow-up. Depression, DM, and male were associated with all sleep disorders at baseline. CVD was associated with the presence of a sleep disorder at baseline and worse sleep quality at the 2-year follow-up; whereas a low serum albumin level was associated with the risk of acquiring a sleep disorder at the 2-year follow-up among patients with normal sleep status at baseline.

Vertical Profiles of Volatile Organic Compounds in Suburban Shanghai - Yuhan Liu; Hongli Wang; Shengao Jing; Ming Zhou; Shenrong Lou; Kun Qu; Wanyi Qiu; Qian Wang; Shule Li; Yaqin Gao; Yusi Liu; Xiaobing Li; et al. (Advances in Atmospheric Sciences, 2021)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Computational Model for Simulation of Lifeboat Free-Fall during Its Launching from Ship in Rough Seas - Shaoyang Qiu; Hongxiang Ren; Haijiang Li (Journal of Marine Science and Engineering, 2020)
In order to improve the accuracy of the freefall of lifeboat motion simulation in a ship life-saving simulation training system, a mathematical model using the strip theory and Kane’s method is established for the freefall of the lifeboat into the water from a ship. With the boat moving on a skid, the model of the ship’s maneuvering mathematical group (MMG) is used to model the motion of the ship in the waves. Based on the formula of elasticity and friction theory, the forces of the skid acting on the boat are calculated. When the boat enters the water, according to the analytical solution theory of slamming, the slamming force of water entry is solved. The simulation experiments are carried out by the established model. The results of the numerical simulation are compared with the calculation results of the hydrodynamics software Star CCM+ at water entry under initial condition A in the paper. The position and velocity of the center of gravity of the boat, the angle, and velocity and acceleration of pitch calculated by the two methods are in good agreement. There is a little difference between the values of translation acceleration calculated by the two methods, which is acceptable. This shows that our numerical algorithm has good accuracy. A qualitative analysis is performed to find the safe point of water entry under the condition of different wave heights and two situations of a ship encountering waves. Finally, the model is applied to the ship life-saving training system. The model can meet the system requirements and improve the accuracy of the simulation.

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Genome-wide association study of soybean seed germination under drought stress - Zhangxiong Liu; Huihui Li; Zuowang Gou; Yanjun Zhang; Xingrong Wang; Honglei Ren; Zixiang Wen; Beom-Kyu Kang; Yinghui Li; Lili Yu; Huawei Gao; Dechun Wang; et al. (Molecular Genetics and Genomics, 2020)

Antagonistic activity and protective effect of a Bacillus subtilis isolate against fish pathogen Edwardsiella piscicida - Xiaomeng Ren; Binbin Wu; Feng Zhao; Lingling Qi; Xianfeng Qiu; Ran Li; Sisi Yang; Fuguo Liu; Ganfeng Yi; Xuezhi Ding; Liqiu Xia; Yunjun Sun (Fisheries Science, 2019)

Refined chronology of prehistoric cultures and its implication for re-evaluating human-environment relations in the Hexi Corridor, northwest China - Yishi Yang; Shanjia Zhang; Chris Oldknow; Menghan Qiu; Tingting Chen; Haiming Li; Yifu Cui; Lele Ren; Guoke Chen; Hui Wang; Guanghui Dong (Science China Earth Sciences, 2019)

Evaluation of land surface temperature by comparing FY-3C/VIRR with Terra/MODIS and MSG/SEVIRI data - Caixia Gao; Shi Qiu; Chuanrong Li; Lingli Tang; Lingling Ma; Yonggang Qian; Yongguang Zhao; Lu Ren (International Journal of Remote Sensing, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

Characteristics and Preliminary Causes of Tropical Cyclone Extreme Rainfall Events over Hainan Island - Xianling Jiang; Fumin Ren; Yunjie Li; Wenyu Qiu; Zhuguo Ma; Qinbo Cai (Advances in Atmospheric Sciences, 2018)

Cerebellar Neural Circuits Involving Executive Control Network Predict Response to Group Cognitive Behavior Therapy in Social Anxiety Disorder - MinlanYuan; Yajing Meng; Yan Zhang; Xiaojing Nie; Zhengjia Ren; Hongru Zhu; Yuchen Li; Su Lui; Qiyong Gong; Changjian Qiu; Wei Zhang (The Cerebellum, 2017)

A new method for the stability analysis of geosynthetic-reinforced slopes - Fei Song; Ru-yi Chen; Li-qiu Ma; Geng-ren Cao (Journal of Mountain Science, 2016)

The role of ANAC072 in the regulation of chlorophyll degradation during age- and dark-induced leaf senescence - Shou Li; Jiong Gao; Lingya Yao; Guodong Ren; Xiaoyu Zhu; Shan Gao; Kai Qiu; Xin Zhou; Benke Kuai (Plant Cell Reports, 2016)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Hosting major international events leads to pest redistributions - Shaojian Li; Lei Guo; Shunxiang Ren; Paul J. De Barro; Bao-Li Qiu (Biodiversity and Conservation, 2014)

Using monitoring data of surface soil to predict whole crop-root zone soil water content with PSO-LSSVM, GRNN and WNN - Zhao Lixi; Shui Pengbo; Jiang Fang; Qiu Hengqing; Ren Shumei; Li Yunkai; Zhang Yu (Earth Science Informatics, 2014)

Contributions of Intestine and Plasma to the Presystemic Bioconversion of Vicagrel, an Acetate of Clopidogrel - Zhixia Qiu; Ning Li; Ling Song; Yang Lu; Jing Jing; Harendra S. Parekha; Wenchao Gao; Fengjie Tian; Xin Wang; Shuangxia Ren; Xijing Chen (Pharmaceutical Research, 2014)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

Insulin-like growth factor binding protein-6 interacts with the thyroid hormone receptor α1 and modulates the thyroid hormone-response in osteoblastic differentiation - Jia Qiu; Xiao-Li Ma; Xin Wang; Hong Chen; Bing-Ren Huang (Molecular and Cellular Biochemistry, 2012)

Comparison of biological parameters between the invasive B biotype and a new defined Cv biotype of Bemisia tabaci (Hemiptera: Aleyradidae) in China - Bao-Li Qiu; Fang Dang; Shao-Jian Li; Muhammad Z. Ahmed; Feng-Liang Jin; Shun-Xiang Ren; Andrew G. S. Cuthbertson (Journal of Pest Science, 2011)

Insights into the pH up-shift responsive mechanism of Acidithiobacillus ferrooxidans by microarray transcriptome profiling - Qian Li; Youhua Ren; Guanzhou Qiu; Nuo Li; Hongwei Liu; Zhimin Dai; Xian Fu; Li Shen; Yili Liang; Huaqun Yin; Xueduan Liu (Folia Microbiologica, 2011)

Microarray-based identification of tomato microRNAs and time course analysis of their response to Cucumber mosaic virus infection - Qiu-lei Lang; Xiao-chuan Zhou; Xiao-lin Zhang; Rafal Drabek; Zhi-xiang Zuo; Yong-liang Ren; Tong-bin Li; Ji-shuang Chen; Xiao-lian Gao (Journal of Zhejiang University-SCIENCE B, 2011)

Prevalence of Endosymbionts in Bemisia tabaci Populations and Their In Vivo Sensitivity to Antibiotics - Muhammad Z. Ahmed; Shun-xiang Ren; Xia Xue; Xiao-Xi Li; Gui-hua Jin; Bao-Li Qiu (Current Microbiology, 2010)

Phylogenetic analysis of Bemisia tabaci (Hemiptera: Aleyrodidae) populations from cotton plants in Pakistan, China, and Egypt - Muhammad Z. Ahmed; Shun-Xiang Ren; Nasser S. Mandour; M. N. Maruthi; Muhammad Naveed; Bao-Li Qiu (Journal of Pest Science, 2010)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Effect of temperature on the life history of Eretmocerus sp. nr. furuhashii, a parasitoid of Bemisia tabaci - Bao-Li Qiu; Paul J. De Barro; Shun-Xiang Ren; Cai-Xia Xu (BioControl, 2007)

Evoked membrane potential change in rat optic nerve fiber: Computer simulation - Vincent Cazenave-Loustalet; Qing-Li Qiao; Li-Ming Li; Qiu-Shi Ren (Neuroscience Bulletin, 2007)